2016
DOI: 10.1161/jaha.116.003371
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Markers Associated With Subclinical Coronary Artery Disease: The Multicenter AIDS Cohort Study

Abstract: BackgroundDespite evidence for higher risk of coronary artery disease among HIV+ individuals, the underlying mechanisms are not well understood. We investigated associations of inflammatory markers with subclinical coronary artery disease in 923 participants of the Multicenter AIDS Cohort Study (575 HIV+ and 348 HIV− men) who underwent noncontrast computed tomography scans for coronary artery calcification, the majority (n=692) also undergoing coronary computed tomography angiography.Methods and ResultsOutcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 61 publications
1
59
0
1
Order By: Relevance
“…29, 3638 Studies have shown that elevated inflammatory markers are prevalent in older, frail adults and may play an important role, directly or indirectly, in the pathogenesis of frailty. 13, 39 Also, prior work from MACS has demonstrated that higher levels of inflammatory markers and immune activation were associated with increased coronary atherosclerosis 21, 28 and with frailty 29 . However, we found that among HIV-uninfected men that the association of frailty with the presence of CAC and any coronary plaque remained statistically significant even after adjusting for these key inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…29, 3638 Studies have shown that elevated inflammatory markers are prevalent in older, frail adults and may play an important role, directly or indirectly, in the pathogenesis of frailty. 13, 39 Also, prior work from MACS has demonstrated that higher levels of inflammatory markers and immune activation were associated with increased coronary atherosclerosis 21, 28 and with frailty 29 . However, we found that among HIV-uninfected men that the association of frailty with the presence of CAC and any coronary plaque remained statistically significant even after adjusting for these key inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…13, 21, 28, 29 Serum/plasma levels of inflammatory markers were measured in samples collected on the day of CT and stored at −70°C until the laboratory work was performed at the University of Vermont Laboratory for Clinical Biochemistry Research (Burlington) with assays described previously. 28 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, alcohol use is significantly associated with traditional CVD risk factors, including insulin resistance (type II diabetes; Míguez-Burbano et al, 2009), tobacco use (Cook et al, 2013), and illicit drug use (Conen et al, 2009; Cook et al, 2013; Chitsaz et al, 2013). Third, HIV-infection alone increases systemic inflammation (Shrestha et al, 2014; Bahrami et al, 2016) and immune activation (Maniar et al, 2013; Strategies for Management of Antiretroviral Therapy (SMART) Study Group et al, 2006; Hsue et al, 2009; Neuhaus et al, 2010), which are pathophysiologic responses that contribute to the risk for CVD (Bahrami et al, 2016; Hsu et al, 2016; Hansson, 2005). Chronic inflammation and immune activation can lead to the breakdown of the endothelial walls of the gastrointestinal tract, a process that leads to microbial translocation, which triggers further immune and pro-inflammatory responses (Maniar et al, 2013; D’Abramo et al, 2014; Klatt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%